Platelet Aggregation and Adhesion during Dietary Copper Deficiency in Rats - Lominadze, David G; Saari, Jack T; Miller, Frederick N; Catalfamo, James L; Justus, David E; Schuschke, Dale A (Thrombosis and Haemostasis, 1996)
The role of dietary copper deficiency in platelet-to-endothelial cell adhesion and in platelet-to-platelet aggregation was studied in vitro. Platelets were obtained from male, weanling Sprague-Dawley rats fed purified diets which were either copper-adequate (CuA, 6.3 μg copper/g of diet) or copper-deficient (CuD, 0.3 μg copper/g of diet) for 4 weeks. The platelet adhesion study was performed by adding CuA or CuD platelets either suspended in homologous plasma or in Tyrode buffer salt solution (TBSS) to cultured rat endothelial cells. After a one hour incubation at 37° C non-adhered platelets were removed and counted in a microcytometer. Platelet aggregation in platelet rich plasma (PRP) samples was induced by adding ADP (2 × 10−4 M) and measured in a turbidometric platelet aggregometer. The content of von Willebrand factor (vWF) in platelets and in plasma and the content of fibrinogen in platelets was determined. Platelet adhesion to rat endothelial cells was significantly lower for platelets from CuD rats than for platelets from CuA rats. ADP induced platelet aggregation from CuD rats was significantly higher than platelet aggregation from CuA rats. The content of vWF in platelets and in plasma from CuD rats was significantly lower than in platelets and plasma from CuA rats. However, the amount of fibrinogen in platelets from CuD rats was about 4-fold higher than that in platelets from CuA rats while the plasma fibrinogen was lower in CuD rats than in CuA rats. These studies illustrate that copper deficiency diminishes platelet adhesion to endothelial cells but increases platelet aggregability. The results suggest that these physiological alterations may be the result of decreased platelet vWF and increased platelet fibrinogen during dietary copper deficiency.